Intensity dependence of multiple orbital contributions and shape resonance in high-order harmonic generation of aligned N2 molecules - Jin, Cheng; Bertrand, Julien B.; Lucchese, R. R.; Worner, H. J.; Corkum, Paul B.; Villeneuve, D. M.; Le, Anh-Thu; Lin, Chii Dong (My University, 2012)
We report measurements and theoretical simulations of high-order harmonic generation (HHG) in aligned N2 molecules using a 1200-nm intense laser field when the generating pulse is perpendicular to the aligning one.With increasing laser intensity, the minimum in theHHGspectra first shifts its position and then disappears. Theoretical simulations including the macroscopic propagation effects in the medium reproduce these observations and the disappearance of the minimum is attributed to the additional contribution of HHG from inner orbitals. We also predict that the well-known shape resonance in the photoionization spectra of N2 should exist in the HHG spectra. It is most clearly seen when the generating laser is parallel to the aligning one and disappears gradually as the angle between the two lasers increases. No clear evidence of this shape resonance has been reported so far when using lasers with different wavelengths. Further experimentation is needed to draw conclusions.
Keywords: High-order harmonic generation (HHG); Intensity dependence; Multiple orbital contributions; Shape resonance; Photoionization